2010
DOI: 10.1148/radiol.09091014
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Value of Adenosine-induced Stress Myocardial Perfusion Imaging with Dual-Source CT at Cardiac CT Angiography

Abstract: Purpose:First, to assess the feasibility of a protocol involving stressinduced perfusion evaluated at computed tomography (CT) combined with cardiac CT angiography in a single examination and second, to assess the incremental value of perfusion imaging over cardiac CT angio graphy in a dual-source technique for the detection of obstructive coronary artery disease (CAD) in a high-risk population. Materials and Methods:Institutional review board approval and informed patient consent were obtained before patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
119
0
15

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(140 citation statements)
references
References 28 publications
6
119
0
15
Order By: Relevance
“…Accordingly, combined ICA/ CMR-MPI is sufficient as a reference standard for collecting anatomical and physiological information regarding coronary stenosis. CTP has been widely investigated using various CT scanners, acquisition protocols, study populations, and reference standards and is considered a promising method for imaging myocardial ischemia, comparable to SPECT and CMR-MPI [7][8][9][10][11][12][13][14]. Bettencourt et al [14] demonstrated that CTP is globally inferior to CMR-MPI; however, integrating CTP and CCTA showed similar diagnostic performance to CMR-MPI using FFR as the reference standard for detecting hemodynamically significant CAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, combined ICA/ CMR-MPI is sufficient as a reference standard for collecting anatomical and physiological information regarding coronary stenosis. CTP has been widely investigated using various CT scanners, acquisition protocols, study populations, and reference standards and is considered a promising method for imaging myocardial ischemia, comparable to SPECT and CMR-MPI [7][8][9][10][11][12][13][14]. Bettencourt et al [14] demonstrated that CTP is globally inferior to CMR-MPI; however, integrating CTP and CCTA showed similar diagnostic performance to CMR-MPI using FFR as the reference standard for detecting hemodynamically significant CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, less than half of high-grade stenoses identified using CCTA physiologically cause myocardial ischemia, and concerns have arisen that the use of CCTA-identified coronary artery disease (CAD) may precipitate high rates of unnecessary ICA [5,6]. To address these limitations, pharmacological CT myocardial perfusion imaging (MPI) has emerged as an additional CT method for diagnosing myocardial ischemia and showed satisfactory diagnostic performance compared with single photon emission computed tomography (SPECT)-MPI, fractional flow reserve (FFR), a combination of ICA and SPECT-MPI, and a combination of ICA and cardiac magnetic resonance (CMR)-MPI [7][8][9][10][11][12][13][14]. However, these investigations have been largely limited to the use of single-energy CT, which relies on relative Hounsfield unit density measurements to detect myocardial perfusion deficits.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent studies suggest that cardiac CT myocardial perfusion is feasible and provides functional significance of CAD, the diagnostic accuracy suffers from high false positive findings. [21][22][23] This has been overcome with the use of hemodynamic analysis of blood flow to coronary artery based on numerical simulation using computational fluid dynamic techniques.…”
Section: Prognostic Value Of Ccta In Cadmentioning
confidence: 99%
“…Rocha et al [14] observed incremental value of CTperfusion over CT-angiography to define hemodynamic relevance of a coronary stenosis.…”
mentioning
confidence: 99%
“…Adenosine stress-perfusion imaging [11][12][13][14][15] is feasible and several studies show promising results. The clear advantage of CT in this setting is the complementary evaluation of coronary artery anatomy and myocardial function, which overcomes current shortcomings of CTA.…”
mentioning
confidence: 99%